Difference between revisions of "009A Sample Final 1, Problem 3"
Jump to navigation
Jump to search
Line 1: | Line 1: | ||
<span class="exam">Find the derivatives of the following functions. | <span class="exam">Find the derivatives of the following functions. | ||
− | <span class="exam">a) <math style="vertical-align: - | + | <span class="exam">(a) <math style="vertical-align: -14px">f(x)=\ln \bigg(\frac{x^2-1}{x^2+1}\bigg)</math> |
− | <span class="exam">b) <math style="vertical-align: - | + | <span class="exam">(b) <math style="vertical-align: -3px">g(x)=2\sin (4x)+4\tan (\sqrt{1+x^3})</math> |
{| class="mw-collapsible mw-collapsed" style = "text-align:left;" | {| class="mw-collapsible mw-collapsed" style = "text-align:left;" | ||
!Foundations: | !Foundations: | ||
|- | |- | ||
− | | | + | |'''1.''' '''Chain Rule''' |
|- | |- | ||
− | | | + | | <math>\frac{d}{dx}(f(g(x)))=f'(g(x))g'(x)</math> |
|- | |- | ||
− | | | + | |'''2.''' '''Quotient Rule''' |
− | |||
|- | |- | ||
− | | | + | | <math>\frac{d}{dx}\bigg(\frac{f(x)}{g(x)}\bigg)=\frac{g(x)f'(x)-f(x)g'(x)}{(g(x))^2}</math> |
|- | |- | ||
− | | | + | |'''3.''' '''Trig Derivatives''' |
− | |||
|- | |- | ||
− | | | + | | <math>\frac{d}{dx}(\sin x)=\cos x,\quad\frac{d}{dx}(\tan x)=\sec^2 x</math> |
− | |||
− | |||
− | |||
− | |||
− | |||
|} | |} | ||
+ | |||
'''Solution:''' | '''Solution:''' | ||
Line 37: | Line 31: | ||
|Using the Chain Rule, we have | |Using the Chain Rule, we have | ||
|- | |- | ||
− | | | + | | |
− | + | <math>\begin{array}{rcl} | |
\displaystyle{f'(x)} & = & \displaystyle{\frac{1}{\bigg(\frac{x^2-1}{x^2+1}\bigg)}\bigg(\frac{d}{dx}\bigg(\frac{x^2-1}{x^2+1}\bigg)\bigg)}\\ | \displaystyle{f'(x)} & = & \displaystyle{\frac{1}{\bigg(\frac{x^2-1}{x^2+1}\bigg)}\bigg(\frac{d}{dx}\bigg(\frac{x^2-1}{x^2+1}\bigg)\bigg)}\\ | ||
&&\\ | &&\\ | ||
Line 48: | Line 42: | ||
!Step 2: | !Step 2: | ||
|- | |- | ||
− | |Now, we need to calculate & | + | |Now, we need to calculate <math>\bigg(\frac{d}{dx}\bigg(\frac{x^2-1}{x^2+1}\bigg)\bigg).</math> |
|- | |- | ||
|To do this, we use the Quotient Rule. So, we have | |To do this, we use the Quotient Rule. So, we have | ||
|- | |- | ||
− | | | + | | |
− | + | <math>\begin{array}{rcl} | |
\displaystyle{f'(x)} & = & \displaystyle{\frac{x^2+1}{x^2-1}\bigg(\frac{d}{dx}\bigg(\frac{x^2-1}{x^2+1}\bigg)\bigg)}\\ | \displaystyle{f'(x)} & = & \displaystyle{\frac{x^2+1}{x^2-1}\bigg(\frac{d}{dx}\bigg(\frac{x^2-1}{x^2+1}\bigg)\bigg)}\\ | ||
&&\\ | &&\\ | ||
Line 71: | Line 65: | ||
!Step 1: | !Step 1: | ||
|- | |- | ||
− | | | + | |We need to use the Chain Rule. We have |
|- | |- | ||
| | | | ||
− | + | <math>g'(x)\,=\,8\cos(4x)+4\sec^2(\sqrt{1+x^3})\bigg(\frac{d}{dx}\sqrt{1+x^3}\bigg).</math> | |
|} | |} | ||
Line 80: | Line 74: | ||
!Step 2: | !Step 2: | ||
|- | |- | ||
− | |We need to calculate& | + | |We need to calculate <math>\frac{d}{dx}\sqrt{1+x^3}.</math> |
|- | |- | ||
|We use the Chain Rule again to get | |We use the Chain Rule again to get | ||
|- | |- | ||
| | | | ||
− | + | <math>\begin{array}{rcl} | |
\displaystyle{g'(x)} & = & \displaystyle{8\cos(4x)+4\sec^2(\sqrt{1+x^3})\bigg(\frac{d}{dx}\sqrt{1+x^3}\bigg)}\\ | \displaystyle{g'(x)} & = & \displaystyle{8\cos(4x)+4\sec^2(\sqrt{1+x^3})\bigg(\frac{d}{dx}\sqrt{1+x^3}\bigg)}\\ | ||
&&\\ | &&\\ | ||
Line 93: | Line 87: | ||
\end{array}</math> | \end{array}</math> | ||
|} | |} | ||
+ | |||
{| class="mw-collapsible mw-collapsed" style = "text-align:left;" | {| class="mw-collapsible mw-collapsed" style = "text-align:left;" | ||
!Final Answer: | !Final Answer: | ||
|- | |- | ||
− | | '''(a)''' <math style="vertical-align: -14px">f'(x)=\frac{4x}{x^4-1}</math> | + | | '''(a)''' <math style="vertical-align: -14px">f'(x)=\frac{4x}{x^4-1}</math> |
|- | |- | ||
− | | '''(b)''' <math style="vertical-align: -18px">g'(x)=8\cos(4x)+\frac{6\sec^2(\sqrt{1+x^3})x^2}{\sqrt{1+x^3}}</math> | + | | '''(b)''' <math style="vertical-align: -18px">g'(x)=8\cos(4x)+\frac{6\sec^2(\sqrt{1+x^3})x^2}{\sqrt{1+x^3}}</math> |
|} | |} | ||
[[009A_Sample_Final_1|'''<u>Return to Sample Exam</u>''']] | [[009A_Sample_Final_1|'''<u>Return to Sample Exam</u>''']] |
Latest revision as of 08:08, 10 April 2017
Find the derivatives of the following functions.
(a)
(b)
Foundations: |
---|
1. Chain Rule |
2. Quotient Rule |
3. Trig Derivatives |
Solution:
(a)
Step 1: |
---|
Using the Chain Rule, we have |
|
Step 2: |
---|
Now, we need to calculate |
To do this, we use the Quotient Rule. So, we have |
|
(b)
Step 1: |
---|
We need to use the Chain Rule. We have |
|
Step 2: |
---|
We need to calculate |
We use the Chain Rule again to get |
|
Final Answer: |
---|
(a) |
(b) |